What makes a terrorist economics and the roots of terrorism - Krueger, Alan B. (Princeton Princeton University Press, 2018)
"Why we need to think more like economists to successfully combat terrorism If we are to correctly assess the root causes of terrorism and successfully address the threat, we must think more like economists do. Alan Krueger's What Makes a Terrorist, explains why our tactics in the fight against terrorism must be based on more than anecdote, intuition, and speculation. Many popular ideas about terrorists are fueled by falsehoods, misinformation, and fearmongering. Many believe that poverty and lack of education breed terrorism, despite a wealth of evidence showing that most terrorists come from middle-class and often college-educated backgrounds. Krueger closely examines the factors that motivate individuals to participate in terrorism, drawing inferences from terrorists' own backgrounds and the economic, social, religious, and political environments in the societies from which they come. He describes which countries are the most likely breeding grounds for terrorists, and which ones are most likely to be their targets. Krueger addresses the economic and psychological consequences of terrorism and puts the threat squarely into perspective, revealing how our nation's sizable economy is diverse and resilient enough to withstand the comparatively limited effects of most terrorist strikes. He also calls on the media to be more responsible in reporting on terrorism. Bringing needed clarity to one of the greatest challenges of our generation, this 10th anniversary edition of What Makes a Terrorist features a new introduction by the author that discusses the lessons learned in the past decade from the rise of ISIS and events like the 2016 Pulse nightclub attack in Orlando, Florida".
Prologue to the tenth anniversary edition -- Preface to the first edition -- Introduction -- Who becomes a terrorist? : characteristics of individual participants in terrorism -- Where does terror emerge? : economic and political conditions and terrorism -- What does terrorism accomplish? : economic, psychological, and political consequences of terrorism -- Questions and answers following the lectures.
"With a new prologue by the author."
Original cloth edition published 2007.
Based on a set of three lectures given by the author as part of the Lionel Robbins memorial lecture series at the London School of Economics and Political Science, February 21-23, 2006.
Includes bibliographical references (pages 177-186) and index.
Keywords: Terrorism; Terrorism -- Economic aspects; Terrorists